Religious Values In Song Lyrics Tingkilan - Muhammad Sadli Mustafa (Analisa: Journal of Social Science and Religion, 2015)
This globalization era brought people of East Kalimantan tend to prefer modern music and western music. This cause the local or traditional music art is marginalized. On the other hand, they have a local music art containing a lot of local wisdom. One of them is tingkilan music. Lyrics of tingkilan contain religious values. Therefore, this study intends to find and to describe the religious values in the song lyrics of the tingkilan musical arts. This study uses a qualitative research method. The research shows that in fact some tingkilan song lyrics have a deep religious value. Some of those religious values are thanksgiving favors, learning of the holly Qur’an, the way of eating and drinking in accordance with the Islamic teaching.